2021
DOI: 10.1021/acsami.0c20369
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Interplay of Brønsted Acid and Lewis Acid Sites in MIL-101(Cr) for Cross-Dehydrogenative Coupling of C–H Bonds

Abstract: Cross-dehydrogenative coupling (CDC) is an effective tool for carbon–carbon bond formation in chemical synthesis. Herein, we report a metal–organic framework (MOF) possessing dual Lewis acidic Cr sites and sulfonic acid sites (MIL-101­(Cr)–SO3H) as an efficient catalytic material for direct cross-coupling of xanthene and different nucleophiles using O2 as the oxidant. The highly porous structure of MIL-101­(Cr)–SO3H enables the free access of reactants to the catalytic active sites inside MOF pores. Kinetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Recently, Chen et al [ 163 ] reported the catalytic property of MIL-101(Cr)-SO 3 H for the aerobic cross-dehydrogenation coupling (CDC) reaction ( Scheme 8 ). MIL-101(Cr)-SO 3 H exhibited quite good catalytic activity in CDC reaction with a product yield of 63% and high selectivity of 98%, which was much higher than that of typical commercial solid acid catalysts.…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, Chen et al [ 163 ] reported the catalytic property of MIL-101(Cr)-SO 3 H for the aerobic cross-dehydrogenation coupling (CDC) reaction ( Scheme 8 ). MIL-101(Cr)-SO 3 H exhibited quite good catalytic activity in CDC reaction with a product yield of 63% and high selectivity of 98%, which was much higher than that of typical commercial solid acid catalysts.…”
Section: Applicationsmentioning
confidence: 99%
“…22 A conjugated framing effect promoted the thermally irreversible activation from O 2 to ROS via an EnT event under another photon excitation. The confined effect of the MOF ensured that the in situ formed singlet oxygen ( 1 O 2 ) combined with carbon radicals to generate peroxy radicals, 23 which further interact with the unsaturated coordinated cerium ions to facilitate their hydrolysis to selectively obtain products containing the carbonyl group 24 and recover the mixed-valence oxygen bridge for the next catalytic cycle. 19 As far as we are aware, this represents the first case of a binuclear Ce−MOF as an artificial monooxygenase, which enables a synergistic two parallel photons strategy for the extremely high activity and selectivity for inert C(sp 3 )−H bonds oxidation under mild conditions utilizing environmentally friendly oxygen instead of expensive or toxic oxidants, providing an environmentally benign route for the direct activation and oxidation of inert alkanes.…”
Section: ■ Introductionmentioning
confidence: 95%
“…6). 57 Compared to the pristine MIL-101(Cr), MIL-101(Cr)-SO 3 H exhibited a superior yield and selectivity towards C(sp 3 )-H alkylation due to the synergistic effect between the Lewis acid (Cr clusters) and Brønsted acid (-SO 3 H groups on the linker) sites in its framework. The product yields slightly decreased when large-size starting materials were used.…”
Section: Integrated Anmentioning
confidence: 99%